2009
DOI: 10.1016/j.drugalcdep.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Linking measures of adolescent nicotine dependence to a common latent continuum

Abstract: Using the theoretical model of Nicotine Dependence (ND) operationalized within the Diagnostic and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 50 publications
9
57
2
Order By: Relevance
“…Consistent with past research (Strong et al, 2007(Strong et al, , 2009, we found that symptoms based on the DSM-IV most precisely measure nicotine dependence for both nondaily and daily smokers with moderate to high scores on the dependence construct. Overall, nondaily smokers had lower scores on the dependence construct but displayed considerable variability.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Consistent with past research (Strong et al, 2007(Strong et al, , 2009, we found that symptoms based on the DSM-IV most precisely measure nicotine dependence for both nondaily and daily smokers with moderate to high scores on the dependence construct. Overall, nondaily smokers had lower scores on the dependence construct but displayed considerable variability.…”
Section: Discussionsupporting
confidence: 89%
“…This study provides justification for including DSM-IV symptoms in a measure that encompasses a wide range of symptoms tapping different aspects of smoking among novice adolescent smokers. IRT analysis does not specifically identify systematic differences in symptom endorsement patterns among these groups; however, this study provides support for a measurement approach that combines symptoms from different measures of nicotine dependence (Strong et al, 2009) and considers symptom variability as a way to improve our ability to measure this construct.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations